Identification of stromal differentially expressed proteins in the colon carcinoma by quantitative proteomics. Issue 11 (5th June 2013) - Mu, Yibing; Chen, Yongheng; Zhang, Guiying; Zhan, Xianquan; Li, Yuanyuan; Liu, Ting; Li, Guoqing; Li, Maoyu; Xiao, Zhefeng; Gong, Xiaoxiang; Chen, Zhuchu
Abstract : Tumor microenvironment plays very important roles in the carcinogenesis. A variety of stromal cells in the microenvironment have been modified to support the unique needs of the malignant state. This study was to discover stromal differentially expressed proteins (DEPs) that were involved in colon carcinoma carcinogenesis. Laser capture microdissection (LCM) was captured and isolated the stromal cells from colon adenocarcinoma (CAC) and non‐neoplastic colon mucosa (NNCM) tissues, respectively. Seventy DEPs were identified between the pooled LCM‐enriched CAC and NNCM stroma samples by iTRAQ‐based quantitative proteomics. Gene Ontology (GO) relationship analysis revealed that DEPs were hierarchically grouped into 10 clusters, and were involved in multiple biological functions that were altered during carcinogenesis, including extracellular matrix organization, cytoskeleton, transport, metabolism, inflammatory response, protein polymerization, and cell motility. Pathway network analysis revealed 6 networks and 56 network eligible proteins with Ingenuity pathway analysis. Four significant networks functioned in digestive system development and its function, inflammatory disease, and developmental disorder. Eight DEPs (DCN, FN1, PKM2, HSP90B1, S100A9, MYH9, TUBB, and YWHAZ) were validated by Western blotting, and four DEPs (DCN, FN1, PKM2, and HSP90B1) were validated by immunohistochemical analysis. It is the first report of stromal DEPs between CAC and NNCM tissues. It will be helpful to recognize the roles of stromas in the colon carcinoma microenvironment, and improve the understanding of carcinogenesis in colon carcinoma. The present data suggest that DCN, FN1, PKM2, HSP90B1, S100A9, MYH9, TUBB, and YWHAZ might be the potential targets for colon cancer prevention and therapy.